ESTIMATING THE SECTION ELEVATION ANGLE OF CUBES ON A CUBIC MESH. APPLICATION TO NICKEL MICROSTRUCTURE SIZE ESTIMATION - Germain, Christian; Blanc, Rémy; Donias, Marc; Lavialle, Olivier; Costa, Jean-Pierre Da; Baylou, Pierre (Image Analysis and Stereology, 2011)
This paper discusses two new image analysis methods for estimating the elevation angle of the section plane of a material. These methods are applicable to materials such as nickel base superalloys, the microstructure of which shows cubes arranged on a cubic regular grid. 3-D models were proposed that help interpret the section images and validate our approach. Our first method operates in the Fourier domain, and is based on the estimation of the spatial frequencies of the network of lines observed on the section. The second method is based on the average distance measured between hazy areas. Both methods are independent. Applied to synthetic images or to real material samples, they produce comparable estimations. The values of the elevation angle allow us to cancel the bias associated with the estimation of the material pattern dimensions.